2017
DOI: 10.3892/ol.2017.6597
|View full text |Cite|
|
Sign up to set email alerts
|

Resistance to the mTOR inhibitor everolimus is reversed by the downregulation of survivin in breast cancer cells

Abstract: Abstract. Everolimus (RAD001) is an inhibitor of mammalian target of rapamycin used in combination with exemestane to treat hormone receptor-positive advanced breast cancer. However, not all patients are equally sensitive to RAD001 and certain patients develop resistance. Therefore, the present study analyzed the mechanisms involved in the resistance of breast cancer cells to RAD001 in order to identify a potential tool to overcome it. The effects of RAD001 on the inhibition of cell viability, on the induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…These data reinforce the hypothesis that survivin is a mediator of resistance to chemotherapy and it is suggested that the increase of this protein in cancer tissues is an unfavorable prognostic marker, which is associated with an increased risk of recurrence [25].…”
Section: Survivinsupporting
confidence: 85%
See 1 more Smart Citation
“…These data reinforce the hypothesis that survivin is a mediator of resistance to chemotherapy and it is suggested that the increase of this protein in cancer tissues is an unfavorable prognostic marker, which is associated with an increased risk of recurrence [25].…”
Section: Survivinsupporting
confidence: 85%
“…The positive regulation of survivin contributes to establish resistance to taxanes, kinesin inhibitors and mTOR inhibitors in breast cancer cells, this has been demonstrated by performing survivin inhibition assays in samples resistant to chemotherapy and inducing the anticancer activity of these drugs, and it was found that by suppressing the activity of survivin, chemotherapy provides good results [25].…”
Section: Survivinmentioning
confidence: 99%
“…Recently, in BC cells, survivin, a downstream target of the PI3K/AKT/mTOR pathway, was demonstrated to be involved in drug resistance, especially to taxanes and kinesin inhibitors [31]. Taglieri and colleagues investigated whether survivin was involved in the acquired resistance to everolimus treatment in hormone-sensitive breast tumors, showing that the drug is able to modify survivin expression in vitro in opposite ways with a downregulation in the sensitive cells and an upregulation in the resistant ones [32]. Moreover, the block of survivin upregulation in these cells restored sensitivity to everolimus, suggesting that survivin is a potential target for future treatments [32].…”
Section: Pi3k/akt/mtor Pathwaymentioning
confidence: 99%
“…Taglieri and colleagues investigated whether survivin was involved in the acquired resistance to everolimus treatment in hormone-sensitive breast tumors, showing that the drug is able to modify survivin expression in vitro in opposite ways with a downregulation in the sensitive cells and an upregulation in the resistant ones [32]. Moreover, the block of survivin upregulation in these cells restored sensitivity to everolimus, suggesting that survivin is a potential target for future treatments [32]. The acquired resistance to mTORC1 inhibitors was attributed to compensatory feedback loops involving the activation of oncogenes such as Myc , the upregulation of which is mediated by the transcriptional regulator bromodomain-containing protein 4 (BRD4) [33].…”
Section: Pi3k/akt/mtor Pathwaymentioning
confidence: 99%
“…Aromatase inhibitor based monotherapy is frequently combined with selective small molecule inhibitors of CDK4/6 and mTOR pathways. Long-term treatment involving single agent therapy or multi-agent combination therapy is frequently associated with acquired drug resistance predominantly due to the emergence of cancer stem cells, thereby impacting therapeutic efficacy and promoting disease progression (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%